Art and modern copyright : the contested image - Cooper, Elena (Cambridge intellectual property and information law, 2018)
"This book is the first in-depth and longitudinal study of the history of copyright protecting the visual arts. Exploring legal developments during an important period in the making of the modern law, the mid-nineteenth to early twentieth centuries, in relation to four themes - the protection of copyright 'authors' (painters, photographers and engravers), art collectors, sitters and the public interest - it uncovers a number of long-forgotten narratives of copyright history, including views of copyright that differ from how we think today. As well as considering the distinct nature of the contribution of copyright to the history of the cultural domain accounted for by scholars of art history and the sociology of art, this book examines the value to lawyers and policy-makers today of copyright history as a destabilising influence: in taking us to ways of thinking that differ from our own, history can sharpen the critical lens through which we view copyright debates today"--